2023
DOI: 10.3390/genes14030584
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Whole-Genome Resequencing and RNA Sequencing Data Reveals Selective Sweeps and Differentially Expressed Genes Related to Nervous System Changes in Luxi Gamecocks

Abstract: The Luxi gamecock developed very unique morphological and behavioral features under the special artificial selection of the most famous Chinese gamecocks. There are very few research studies on the genetics and selection of the Luxi gamecock. We used six methods (Fst, Tajima’s D, hapFLK, iHS, XP-EHH, and Runs of homozygosity) to detect selective sweeps in whole-genome resequencing data of 19 Luxi gamecocks compared to other Chinese indigenous chickens. Eleven genes that were highly related to nervous system de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 75 publications
0
0
1
Order By: Relevance
“…Additionally, the average alignment rate was 99.78%. Our Q20 or Q30 rates were substantially higher than those reported by Shuli et al ( 26 ) and Wei et al ( 27 ), while the alignment rate of our data was higher than that achieved by Yin et al ( 28 ) and Zhou et al ( 29 ). This indicated that our sequencing data were of sufficient quality for use in subsequent analysis.…”
Section: Discussioncontrasting
confidence: 88%
“…Additionally, the average alignment rate was 99.78%. Our Q20 or Q30 rates were substantially higher than those reported by Shuli et al ( 26 ) and Wei et al ( 27 ), while the alignment rate of our data was higher than that achieved by Yin et al ( 28 ) and Zhou et al ( 29 ). This indicated that our sequencing data were of sufficient quality for use in subsequent analysis.…”
Section: Discussioncontrasting
confidence: 88%